LEADER IN THE SCHOOL NOWADAYS: THEORY AND EXPERIENCE - Muzis, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
It is the 21century when everything is subjected to continuous and rapid changes. The human being should be able to adapt to changes in labor market, in the technological world and in globalized life. To operate successfully in free market conditions, the whole economy in Latvia, including all schools, has had to implement constant change. Economic transition demanded from Latvia school heads and teachers radical change in thinking and behavior. The main issue of article is leadership talent identification, development, succession and retention in contextually different primary and secondary schools in Latvia. Quality schools require quality leaders. It is vital that their morale, professional commitment, and sense of professional value and personal worth is maintained, and their creativity and enthusiasms is promoted. Paper will explore leadership talent identification, development, succession and retention in schools. The crucial question is how to achieve heads and teachers commitment to leadership in schools.